The Effect of Tourist Attractions and Facilities on Visiting Decisions Through Visiting Interest as an Intervening Variable at Guci Tegal Hot Spring Tourism Object (Case Study of Visitors to Guci Tegal Hot Spring Tourist Object) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study examines the influence of tourist attractions and facilities on the decision to visit Guci Tegal Hot Springs, with interest in visiting as an intervening variable. Data were obtained from visitor questionnaires and analyzed using SEM-PLS through SmartPLS. The results show that attractions and facilities have a significant effect on visiting interest, which in turn affects visiting decisions. Visiting interest is proven to mediate the relationship between the two variables on visiting decisions
Keywords: tourist attraction; facilities; visit interest; visit decision